Design Build Winner Selection Application In Tender Process In Institute Business and Informatics Stikom Surabaya - Luhkitasari, Alifianti Putri; Wibowo, Januar; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Institute of Business and Informatics Stikom Surabaya is a college in Surabaya that needs needs in running daily operations, such as the need for alma mater suits, t-shirts, and others. Needs are needed in quantities that are not small. In order to get the minimum price and maximum quality, Institute of Business and Informatics Stikom Surabaya is a college in Surabaya held several tenders. The bidding process is currently conducted with a jury assessing the bidders by giving points 0 to 100 according to the assumption of the tender jury itself. There is no standardization of points against the assessment criteria. Unlisted or documented reasons the jury gives points against offers from participants. The percentage weight of each criterion is the same, so the actual criterion is more important than the other criterion is considered equal weight. These matters cause the possibility of misstatement of tendering and tender selection.The solution needed to overcome the above problems is the assessment by using scoring system method. Scoring system method is used to assist decision makers in determining the eligibility of bidders to be included in the list of alternatives to tender winner selection. To minimize the risks of winning the selection of winners in the tender process, it is necessary to calculate the percentage of priority weight.Based on the results of manual scoring system testing and calculation results by the system, obtained the result that there is no difference between the calculation manually with the calculation by the application so that the application can perform calculations accurately. The trial results show three tender reports with three judges and each tender has three participants and the result is between manually and calculated by the application.